Great Reset—Opportunity or Threat? Business Systems Laboratory International Symposium, Palermo, Italy, 2024 - Vătămănescu, Elena-Mădălina; Dominici, Gandolfo (Springer Proceedings in Business and Economics, 2024)
X, 208 p. 22 illus., 13 illus. in color.